2012
DOI: 10.1557/opl.2012.1140
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of 4H-SiC Epitaxial Layer Quality on Growth Conditions with Wafer Size Corresponding to 150 mm

Abstract: Homoepitaxial growth on 4H-SiC Si-face substrates with sizes corresponding to 150 mm was carried out. The influence of growth conditions for uniformity and epitaxial defect density was investigated. A 150 mm size was realized by using two 76.2 mm wafers lined up in a radial direction. C/Si ratio is found to be a major parameter for controlling triangular defect density and the generation of step bunching. As a result, the surface morphology without bunched step structure and the triangular defect density with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…wafers on the rotating susceptor. [26][27][28] The precursor gases used were monosilane and propane in hydrogen atmosphere. Every epitaxial growth was performed without intentional nitrogen doping.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…wafers on the rotating susceptor. [26][27][28] The precursor gases used were monosilane and propane in hydrogen atmosphere. Every epitaxial growth was performed without intentional nitrogen doping.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The epitaxial growth was carried out using the chemical vapor deposition (CVD) system as in the previous study [2,5,6]. Precursor gases used were monosilane and propane in hydrogen atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…In spite of being considered more difficult to improve doping uniformity on C-face, the recent reports imply that the requirement for the uniform doping has gathered more attention for large diameter substrates, such as 150 mm diameter [2][3][4]. In the previous study, using a multiple-wafer (3×150-mm diameter) epitaxy system with a horizontal low-pressure hot-wall reactor [5,6], it was shown on C-face that the background donor level was low enough to control the required nitrogen doping concentration for the drift layer of high blocking voltage power MOSFETs, such as 3.3 kV devices [2]. In the current work, guidelines necessary to improve the doping uniformity have been examined as far as the practical throughput is maintained, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We have already reported that such defects can be effectively suppressed by increasing the growth temperature or reducing C/Si ratio. 31 Regarding the growth temperature, it is difficult to apply high growth temperature, in light of the step bunching described above. In addition, such defects are typically generated at the interface between the epitaxial layer and the substrate.…”
Section: P549mentioning
confidence: 99%